Family support and breastfeeding satisfaction in adolescent mothers - Budiarti, Lola Kumala; Fatmawati, Ariani; Imansari, Bhekti (Media Keperawatan Indonesia, 2024)
The mother's behavior in giving breast milk, which can affect breastfeeding satisfaction, is one of the achievements of the mother's role. Breastfeeding satisfaction is a key factor in the success of exclusive breastfeeding programs, where family support is an important factor that can influence breastfeeding satisfaction. The purpose of this study was to determine the relationship between family support and breastfeeding satisfaction in adolescent mothers. In this study, the method used was a descriptive correlation with a cross-sectional approach. The sample set was 61 people with inclusion criteria. A questionnaire based on the Maternal Breastfeeding Evaluation Scale (MBFES) and a questionnaire based on Family Support were used to collect data. The bivariate analysis technique with chi-square. The results of this study showed a p-value 0,000 that there is a relationship between family support and breastfeeding satisfaction in adolescent mothers. Breastfeeding satisfaction is influenced by family support because most adolescent mothers consult with their parents and husbands before deciding to breastfeed their children.